PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 017 RANAH SINGKUANG - Meri Anggia Murni; Mahmud Alpusari; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning IPA study class IV SDN 017 Ranah Singkuang. KKM achieved by school was 75. From 27 students who achieve KKM just 10 students (37.04%) while students who did’nt achieve KKM is 17 students (62.96%) with a class average of 58.66. The purpose of this research to improve learning outcomes IPA class IV SDN 017 Ranah Singkuang with the application of learning models Inquiry. The results obtained by the average value of 58.66 basic score increased in the first cycle of 18.44% to 69.48. In the second cycle the average value of students also increased by 33.34% to 78.22. On the basic of classical completeness score IPA student learning outcomes is only 37.04% (not finished). After the professor of applied learning model Inquiry in the first cycle classical completeness increased to 44.44% (not finished), and the second cycle of classical completeness obtained are increased to increase to 88.89%. Activities of teachers at the first meeting of first cycle acquire a percentage of 66% with enough categories. The second meeting increased to 75% in enough categories. In the first meeting of second cycle increased to 91% with good category. At the second meeting increased to 95% with good category. Activities of students in the first meeting of the first cycle acquire a percentage of 54% with enough categories. The second meeting increased to 71% in enough categories. In the first meeting of the second cycle increased to 83% with good category. At the second meeting increased to 92% with good category.Keywords : Inquiry, learning outcomes IPA